Agile contracting as a mechanism to improve performance in business environments - Gabriel Silva-Atencio; Cynthia López-Valerio (Dyna)
During the initial phase of the Industry 5.0 revolution, agile methodologies have become crucial in companies, especially for projects that aim to establish a competitive advantage in this new era. The purpose of this research is to evaluate how flexibility in contractual clauses impacts the performance of agile projects, particularly in the context of Industry 5.0. Using a quantitative, exploratory, descriptive and cross-sectional approach; where, inclusion criteria were applied that considered only professionals with certifications in agile methodologies and proven experience in project management in public and private sectors. The final sample (100 participants) was selected from a universe of 1,000, ensuring representativeness by sector and management role. The analysis revealed that 82% of respondents believe that contractual flexibility significantly improves the achievement of project objectives, with the main factors being: 1) adaptability (72%); 2) flexibility (82%); 3) continuous learning (84%); speed (87%), teamwork (81%); and customer focus (87%) contribute to flexibility and collaboration among project participants contribute significantly to effectively meeting contractual conditions. In addition, the findings underscore the importance of rapidly improving the knowledge, skills and experience of staff in agile environments. The study advocates external support to accelerate the acquisition of contextual expertise, mitigate risks and foster a culture of innovation in organizations.